Melania the Younger from Rome to Jerusalem - Clark, Elizabeth A. 1938-2021 (Oxford University Press, 2021)
"Melania the Younger: From Rome to Jerusalem analyzes one of the most richly detailed stories of a woman of late antiquity. Melania, an early fifth-century Roman Christian aristocrat, renounced her many possessions and staggering wealth to lead a life of ascetic renunciation. Hers is a tale of "riches to rags." Born to high Roman aristocracy in the late fourth century, Melania encountered numerous difficulties posed by family members, Roman officials, and historical circumstances themselves in disposing of her wealth, property spread across at least eight Roman provinces, and thousands of slaves. Leaving Rome with her entourage a few years before Alaric the Goth's sack of Rome in 410, she journeyed to Sicily, then to North Africa (where she had estates upon which founded monasteries), before settling in Jerusalem. There, after some years of semi-solitary existence, she founded more monastic complexes. Towards the end of her life, she traveled to Constantinople (present-day Istanbul) in an attempt to convert to Christianity her still-pagan uncle, who was on a state mission to the eastern Roman court. Throughout her life, she was accustomed to meet and be assisted by emperors and empresses, bishops, and other high dignitaries. Embracing a fairly extreme asceticism, Melania died in Jerusalem in 439. Her Life, two versions of which (Greek and Latin) were discovered in the late nineteenth- and early twentieth centuries, was composed by a long-time assistant who succeeded her in the direction of the male and female monasteries in Jerusalem. An English translation of the Greek version of her Life accompanies the text of this nine-chapter book"--
Enthält eine Übersetzung von: The Life of Saint Melania the Younger.
Keywords: Melania -- Heilige -- 383-439; Geschichte 383-439; Hagiografie; Melania / the Younger, Saint / 385?-439; Melania / the Younger, Saint / 385?-439 / Homes and haunts; Christian women saints / Biography; Christian women saints; Homes; Biographies; Biografie